Mediterranean versus Western Diet Effects on Caloric Intake, Obesity, Metabolism, and Hepatosteatosis in Nonhuman Primates. Issue 5 (23rd April 2019) - Shively, Carol A.; Appt, Susan E.; Vitolins, Mara Z.; Uberseder, Beth; Michalson, Kristofer T.; Silverstein‐Metzler, Marnie G.; Register, Thomas C.
Abstract : Objective: This study aimed to determine the effects of humanlike Western and Mediterranean diets on caloric intake, obesity, metabolism, and hepatosteatosis in an established nonhuman primate model of obesity, cardiometabolic syndrome, type 2 diabetes, and atherosclerosis. Methods: A 38‐month, randomized, preclinical, nonhuman primate primary prevention trial of 38 socially housed, middle‐aged adult females was conducted. The monkeys were characterized during a 7‐month baseline phase while consuming chow and then randomized to either Western or Mediterranean diets; the groups were balanced on baseline characteristics. Western and Mediterranean diets were formulated to closely reflect human diets, matched on macronutrient content, with protein and fat derived largely from animal sources in the Western diet and plant sources in the Mediterranean diet. Food consumption, activity levels, energy expenditure, body composition, carbohydrate metabolism, and hepatosteatosis were measured during baseline and treatment phases. Results: The Western diet increased caloric intake for the first 6 months and body fat, activity, energy expenditure, insulin resistance, and hepatosteatosis after 2.5 years, whereas the Mediterranean diet reduced triglyceride levels. Conclusions: This is the first report of differential caloric intake and obesity with long‐term consumption of a Western versus Mediterranean diet under controlled experimental conditions and the first experimental evidence that a Mediterranean diet protects against hepatosteatosis compared with a Western diet.